Formulation of Customary Criminal Sanctions From a Human Rights Perspective - Erni Dwita Silambi; Rosnida Rosnida; Enni Eka kusumawati (Jurnal Hukum Volkgeist, 2022)
The provision of customary criminal sanctions varies according to the customs and norms that apply in an area and this research takes a case study in Merauke Papua. This research focuses on the provision of customary sanctions for perpetrators which will be viewed from the point of view of human rights. This study aims to see and analyze the criminal sanctions given to the perpetrators and whether these sanctions do not conflict with the human rights that apply in Indonesia.